Nanotechnological Approaches to Therapeutic Delivery Using Elastin-Like Recombinamers - Rodríguez-Cabello, José Carlos; Piña, María Jesús; Ibáñez-Fonseca, Arturo ; 0000-0002-2223-5041; Fernández-Colino, Alicia; Arias, Francisco Javier (Bioconjugate Chemistry, 2015)
This Review discusses the use of elastin-like polymers and their recombinant version, elastin-like recombinamers, in drug-delivery systems. These macromolecules exhibit a number of interesting properties that are rarely found together in any other family of materials, especially extremely high biocompatibility, high bioactivity and functionality, complex yet fully controlled composition, and stimuli responsiveness. Appropriate design of these molecules opens up a broad range of different possibilities for their use in new therapeutic platforms. The first of these described herein is the use of ELRs in single-molecule devices as therapeutic entities in their own right. Subsequently, we describe how the self-assembly properties of these materials can be exploited to create nanocarriers and, eventually, microcarriers that are able to temporally and spatially control and direct the release of their drug load. Intracellular drug-delivery devices and nanocarriers for treating cancer are among the uses described in that section. Finally, the use of ELRs as base materials for implantable drug depots, in the form of hydrogels, is discussed.
Keywords: Animals; Drug Carriers/chemistry; Drug Delivery Systems/methods; Elastin/chemistry; Humans; Hydrogels/chemistry; Nanotechnology/methods; Recombinant Proteins/chemistry